Genetic variation in long noncoding RNAs and the risk of nonalcoholic fatty liver disease - Sookoian, Silvia Cristina (2017)
The human transcriptome comprises a myriad of non protein-coding RNA species, including long noncoding RNAs (lncRNAs), which have a remarkable role in transcriptional and epigenetic regulation. We hypothesized that variants in lncRNAs influence the susceptibility to nonalcoholic fatty liver disease (NAFLD). Using next generation sequencing, we performed a survey of genetic variation associated with randomly selected lncRNA-genomic regions located within both experimentally validated and computationally predicted regulatory elements. We used a two-stage (exploratory, n = 96 and replication, n = 390) case-control approach that included well-characterized patients with NAFLD diagnosed by liver biopsy. We sequenced > 263 megabase pairs at quality score > Q17, in a total of 2,027,565 reads, including 170 lncRNA-genomic regions. In the sequencing analysis and the validated dataset, we found that the rs2829145 A/G located in a lncRNA (lnc-JAM2-6) was associated with NAFLD and the disease severity. Prediction of regulatory elements in lnc-JAM2-6 showed potential sequence-specific binding motifs of oncogenes MAFK and JUND, and the transcription factor CEBPB that is involved in inflammatory response. The A-allele was significantly associated with NAFLD as disease trait (p = 0.0081) and the disease severity (NASH-nonalcoholic steatohepatitis vs. controls: OR 2.36 [95% CI: 1.54-3.62], p = 0.000078). The A-allele carriers also have significantly higher body mass index and glucose-related traits compared with homozygous GG. Hence, our results suggest that variation in lncRNAs contributes to NAFLD severity, while pointing toward the complexity of the genetic component of NAFLD, which involves still unexplored regulatory regions of the genome.